Answer:
-1 3/4
Step-by-step explanation:
3/4 + (-2 1/2)
3/4 - 2
-1 3/4
Your answer should be 81 for a. I got this result by multiplying 9 by 9.
12 x 12 = 144
144 / 58 = 2.66
Quadratic polynomial x^2 - x - 6 = f(x)
binomial (x-3)
dividing:-
x + 2
----------------------
x - 3 ) x^2 - x - 6
x^2 - 3x
----------
2x - 6
2x - 6
--------
.........
result of division is (x + 2)
s o we can write the function as (x - 3)(x + 2)
Part 2 f(a) = f(3) = (3)^2 - 3 - 6 = 0
Part3 The remainder Theorem states that the remainder when a polynomial is divided by (x - a) then the remainder is f(a). If f(a) = 0 then x - a is a factor.
In the above case f(3) = 0 therefore (x - 3) is a factor of our polynomial.